2013
DOI: 10.5424/fs/2013223-04135
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Forest Management in a Mediterranean region: Social preferences

Abstract: Aim of study: There is a lack of empirical research that deals with sustainable forest management in Mediterranean regions, among the most vulnerable ecosystems. The main purpose of this work is to define the strategic criteria and objectives for sustainable forest management and aggregate the preferences of stakeholders in a Mediterranean region, using AHP and Goal Programming.Area of study: Valencian Community (Spain).Material and Methods: Firstly, we identified forest stakeholders and structured a decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…AHP, the method developed by Saaty [29], which has been broadly used in different fields [30][31][32][33], is implemented to obtain the relative weights of the TEV components, while DCF [34] is used to determine the economic values of the services associated with DUV.…”
Section: Methodsmentioning
confidence: 99%
“…AHP, the method developed by Saaty [29], which has been broadly used in different fields [30][31][32][33], is implemented to obtain the relative weights of the TEV components, while DCF [34] is used to determine the economic values of the services associated with DUV.…”
Section: Methodsmentioning
confidence: 99%
“…Unsustainable forest resource exploitation, especially in developing countries for economic growth, has contributed to global warming, climate change, health issues, poor yield and extinction of certain plant and animals species [6]. Studies have shown that deforestation continuously triggers drought and dry spell issues in most part of Africa hence threatening food security and poverty alleviation on the continent [7].…”
Section: Introductionmentioning
confidence: 99%
“…AHP could also be useful to select and prioritise strategic alternatives in the management of ESS, by using pairwise comparison of the performance of alternatives in relation to every ESS. However, empirical studies have shown that only the most expert stakeholders are capable of meeting the consistency requirement of the method when comparing alternatives with respect to technical performances (Maroto et al, 2013). Thus, AHP is advisable for selecting and ranking alternatives when there are no data available for the indicators for ESS.…”
Section: Discussionmentioning
confidence: 99%
“…Ecosystem maintenance is the priority function, being a result consistent with the previous regional studies. Products from forests, mainly timber, have little relevance due to the slow regenerative capacity of the Mediterranean forests (Maroto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation